Diversity of Macroscopic Fungal Types in South Leitimur District, Ambon City - Ebedh Barlef Lorwens; Jogeneis Patty; Costanza Uruilal (Universitas Pattimura, 2022)
Macroscopic fungi are eukaryotic, heterotrophic, cosmopolitan organisms, have fruit bodies large enough to be seen without using tools, and vary in morphology, size, and color. This research was carried out in two villages in Leitimur Selatan District, Ambon City, namely Hutumuri and Ema, from May 2022 to July 2022. Macroscopic fungal samples were obtained during a survey using the exploration method. Sampling locations were based on predetermined transect lines and random fungal samples were taken at each location. Identification in the laboratory was carried out to determine the type of mushroom, fruit body shape, color, and size of the mushroom. The data obtained was then analyzed qualitatively and quantitatively. The research results obtained 32 species of fungi consisting of two divisions, namely Ascomycota and Basidiomycota, as well as 18 families. The frequency of the presence of fungi in Leitimur Selatan District was the highest at 19.6% and the lowest at 0.1%, and the fungal populations found lived either alone or in colonies. Based on Hierarchical Cluster Analysis (HCA), macroscopic fungi at the research location were divided into two large groups with a dissimilarity coefficient of 31%. The main differentiating character based on Principle Component Analysis (PCA-Biplot) found that the characteristic character in the descriptor of seven fungal species was the lamella character, and the differentiating character in the descriptor of two fungal species was the pore characteristics and pore size.